The Effect of Body Mass Index on Post-Bolus Magnesium Levels in the Obstetric Patient - De Zoysa, Madushka Y.; Westermann, Melissa; Yang, Tyler; Chung, Judith H. (American Journal of Perinatology, 2023)
Objective In the setting of a growing obese obstetric population, we sought to determine whether differences in body mass index (BMI) and obesity class influenced both serum magnesium levels and the likelihood of achieving therapeutic levels for eclampsia prophylaxis after standard boluses of magnesium sulfate.Study Design This is a retrospective cohort study of patients treated with magnesium sulfate in the setting of either preeclampsia with severe features or preterm labor between 2010 and 2016. Subjects were categorized by BMI: Normal (BMI < 30 kg/m2), Class 1 (BMI 30–34.9 kg/m2), Class 2 (BMI 35–39.9 kg/m2), and Class 3 (BMI ≥ 40 kg/m2). Study participants' demographics, intrapartum characteristics, and adverse reactions were compared among the groups. Logistic regression models were used to calculate unadjusted and adjusted odds ratios comparing the likelihood of each BMI class reaching therapeutic eclamptic prophylactic levels. Linear regression models were also evaluated to determine the relationship between BMI and post-bolus serum magnesium levels.Results Of the 760 people who met the inclusion criteria, 313 (41.1%) had normal BMI, 190 (25.0%) had Class 1 obesity, 135 (17.8%) had Class 2 obesity, and 122 (16.1%) had Class 3 obesity. When adjusted for confounders, those with Class 1 obesity were 54% less likely to achieve serum levels deemed therapeutic for seizure prophylaxis compared with normal BMI counterparts. Meanwhile, those with Class 2 or 3 obesity were 90% less likely. Linear regression models also demonstrated an inverse association between BMI and post-bolus serum magnesium levels.Conclusion Increasing BMI has a significant effect on post-bolus serum magnesium levels regardless of standard loading dose used. Immediately after bolus administration, obese gravidas are significantly less likely to reach levels effective for eclamptic seizure prophylaxis. When considering which bolus to administer in an obese gravida, it may be more beneficial to choose a 6 g load.Key Points
Keywords: magnesium; preeclampsia; obesity; body mass index; preterm labor